„Poznam Cię światełkami palców” – o inspirującym wpływie Lasek na twórczość księdza Jana Twardowskiego - Bohdziewicz-Sulecka, Beata (Colloquia Litteraria, 2023)
The article is a voice in the reflection on the culture-forming role of Laski, where Róża Czacka has been running the Society for the Care of the Blind since 1922. It is also a haven for those who have lost their sight of faith, a place of evangelical work and many creative inspirations. I show how the Laski community influenced Jan Twardowski’s post-war debut and his poetry. Referring to M. Czermińska’s article, I call Laski the poets autobiographical place. I interpret poems inspired by Twardowski’s stays and meetings in Laski, emphasizing the theme of sensual experience, mainly touch